Finding and verifying enhancers for endothelial-expressed genes - Neal, A; Rodriguez-Caro, H; De Val, S (Humana Press, 2022)
Identification and analysis of enhancers for endothelial-expressed genes can provide crucial information regarding their upstream transcriptional regulators. However, enhancer identification can be challenging, particularly for people with limited access or experience of bioinformatics, and transgenic analysis of enhancer activity patterns can be prohibitively expensive. Here we describe how to use publicly available datasets displayed on the UCSC Genome Browser to identify putative endothelial enhancers for mammalian genes. Furthermore, we detail how to utilize mosaic Tol2-mediated transgenesis in zebrafish to verify whether a putative enhancer is capable of directing endothelial-specific patterns of gene expression.